Clinical and refractive outcomes after topography-guided refractive surgery planned using Phorcides surgery planning software. Issue 9 (September 2022) - Stulting, R. Doyle; Lobanoff, Mark; Mann, Paul M.; Wexler, Stephen; Stonecipher, Karl; Potvin, Richard
Abstract : Excellent outcomes can be obtained with topography-guided LASIK using Contoura Vision when the Phorcides Analytical Engine is used to program the WaveLight EX500 excimer laser. Abstract : Purpose: To evaluate prospectively the clinical outcomes of topography-guided laser in situ keratomileusis (LASIK) surgery performed with Contoura Vision using the Wavelight excimer laser and planned with the Phorcides Analytical Engine. Setting: Four clinical practices in the U.S. Design: Prospective single-arm interventional study. Methods: 130 eyes of 65 patients with myopia or myopic astigmatism were enrolled in a prospective study of visual and refractive outcomes after treatment with Contoura Vision using the Wavelight EX500 excimer laser to achieve optimal distance vision. At 3 months postoperatively, uncorrected distance visual acuity (UDVA), manifest refraction, and corrected distance visual acuity (CDVA) were measured and compared with previously published studies. Results: At 3 months postoperatively, 100%, 89%, and 28% of eyes achieved UDVA of 20/20, 20/15, and 20/12.5 or better, respectively. 92% of eyes had postoperative UDVA equal to or better than their preoperative CDVA. Postoperative CDVA was equal to, 1 line better, or 2 lines better than the preoperative CDVA in 53%, 40%, and 6% of eyes, respectively. Only 1 eye lost 1 line of CDVA, and no eyes lost more than 1 line of CDVA. A statistically significant decrease was noted in subjective visual complaints, including glare, halos, difficulty driving at night, reading difficulty, starbursts, fluctuation in vision, and light sensitivity. Conclusions: The Phorcides Analytical Engine can be used to optimize visual outcomes for the correction of myopia and myopic astigmatism.